Prototype Design and Application of a Semi-circular Automatic Parking System - Atacak, Ismail; Erdogdu, Ertugrul (International Journal of Intelligent Systems and Applications in Engineering, 2017)
Nowadays, with the increasing population in urban areas, the number of vehicles used in traffic has also increased in these areas. This has brought with it major problems that are caused by insufficient parking areas, in terms of traffic congestion, drivers and environment. In this study, in order to overcome these problems, a multi-storey automatic parking system that automatically performs vehicle recognition, vehicle parking, vehicle delivery and pricing processes has been designed and the practical application of this system has been realized on a prototype. The vehicle recognition process in the designed system has been fulfilled through a software prepared on the personal computer connected to the webcam. A multi-storey semi-circular structure has been used as a parking area to resolve parking area deficiencies. Therefore, the carrying system that carries out the parking process in the system has been designed as a cylindrical coordinated robot that can move horizontally, vertically and in the forward-back direction. The control of whole system has been realized by PIC16F877A microcontroller. The results obtained from the prepared prototype have showed that the proposed system can provide significant contributions to the solution of problems resulting from parking area deficiencies.